Kajian Implementasi Kebijakan Pengelolaan Sampah Menggunakan Soft System Methodology di Kota Bandung - Medina Andini Herman; Endang Wirjatmi Trilestari (Public Service and Governance Journal, 2025)
The growth of population and rapid urbanization in metropolitan areas have triggered a significant increase in waste volume, including in the city of Bandung. This study aims to analyze the implementation of waste management policies using the Soft System Methodology (SSM), particularly through the CATWOE analysis framework. The research was conducted in three sub-districts with distinct characteristics—Coblong, Arcamanik, and Cinambo through in-depth interviews with key stakeholders and field observations. The findings reveal that programs such as Kang Pisman and TPS3R face major challenges related to public participation, cross-sectoral coordination, and limited resources. The CATWOE analysis identifies the need for system improvement by considering the perspectives of all stakeholders: the community (Customer), technical implementers (Actor), policy makers (Owner), and external environmental factors (Environment) that influence the effectiveness of waste management policies.